(untitled) (Quinto Sol, 2011)
The celebration of the 200 years of the May Revolution invites us to review History, its interpretations and its teaching. To do this, it is necessary to have a look at school, which is a key institution in the reproduction of patriotic narratives from the past. It is expected to make an approach to the school commemorative practices with the aim of investigating how permeable the school is before the new knowledge and disciplinary perspectives. The resistance of some practices that persist within institutions will also be taken into account. The possibility of incorporating disciplinary updating in History teaching will allow us to construct more historiographic visions of the past so as to denaturalize the “mythical” accounts of the national past. The sample that supports this investigation is made up of a set of school ceremonies held in primary schools from the city of General Pico. This work intends to contribute to the reflection on school practices, its connection with the area of Social Sciences and the relationship between the spaces of historiographic production and those spreading strategies which allow the incorporation of disciplinary updating in the school field.